2020
DOI: 10.3389/fimmu.2020.01746
|View full text |Cite
|
Sign up to set email alerts
|

hUCMSCs Mitigate LPS-Induced Trained Immunity in Ischemic Stroke

Abstract: Innate immune memory is a part of the innate immune system that facilitates the elimination of pathogens. However, it may exacerbate neuropathology. In this study, we found that innate immune memory is detrimental in stroke, because it promotes the acute immune response and exacerbates ischemic infarcts. Mesenchymal stem cell therapy has been widely studied for its therapeutic potential in various diseases including stroke, but whether it diminishes innate immune memory has not been studied. Here, our study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Our previous study found that MSCs could alleviate trained immunity through the inhibition of H3K4 methylation (Feng et al, 2020). Although MSC therapy shows potential regarding the mitigation of neuropathologies, the main distribution of MSCs after their intravenous injection is mostly restricted to the lungs, indicating that the therapeutic effect of MSCs occurs mainly via a paracrine-mediated mechanism (Gnecchi et al, 2016;Sherman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study found that MSCs could alleviate trained immunity through the inhibition of H3K4 methylation (Feng et al, 2020). Although MSC therapy shows potential regarding the mitigation of neuropathologies, the main distribution of MSCs after their intravenous injection is mostly restricted to the lungs, indicating that the therapeutic effect of MSCs occurs mainly via a paracrine-mediated mechanism (Gnecchi et al, 2016;Sherman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in regenerative medicine have revealed the great potential of mesenchymal-stem cells (MSCs) in brain repair based on their remarkable anti-inflammatory and immunomodulatory properties (Galindo et al, 2011;Sherman et al, 2019). Our previous study found that MSCs triggered the remission of trained immunity through the inhibition of H3K4 methylation (Feng et al, 2020). However, concerns regarding their safety as well as their tumor-or microinfarction-inducing potential limit the translational capacity of MSCs (Kunter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The bilateral carotid artery stenosis (BCAS) model was performed as described previously (Feng et al, 2020b ). Briefly, the mice were anesthetized using 4% isoflurane in 28% O 2 and 68% N 2 and maintained on 2% isoflurane in 29% O 2 and 69% N 2 by a mask.…”
Section: Methodsmentioning
confidence: 99%
“…From the limited studies on WML, evidence shows that the Dl-NBP could promote the cognitive function in VaD models caused by chronic hypoperfusion (Li et al, 2019 ). The normal cognitive function requires a relatively normal electronic signal and a synaptic signal, which rely on intact myelin, as well as cholinergic neurotransmission (Feng et al, 2020b ). The beneficial effects of Dl-NBP on VaD were demonstrated by improving remyelination and enhancing the function of the cholinergic system (Tian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the secretion of trophic factors and antiapoptotic molecules that promote neurogenesis and angiogenesis is increased. Some studies have also reported the use of human umbilical cord-derived MSCs for ischemic stroke treatment (Feng et al, 2020 ; Noh et al, 2020 ).…”
Section: Stem Cell Types For Treatment Of Ischemic Strokementioning
confidence: 99%